Effect of the preparation method on the drug loading of alginate-chitosan microspheres (eXPRESS Polymer Letters)
Alginate-chitosan (ALG-CHI) microspheres obtained by polyelectrolyte complexation are pH-sensitive, biocompatible and adhesive, and are excellent candidates for the delivery of drugs, proteins and peptides in the human body. A wide variety of methods for the production of these polymeric complexes has been provided. The water-in-oil emulsion is a complex production method, but generally enhances the control of particle size and particle size distribution of the microspheres, extremely necessary for obtaining repeatable controlled release behavior. In this work, a novel and facile water-in-oil emulsion method for the ALG-CHI polyelectrolyte complexes is discussed. The method proposed produced ALG-CHI microspheres with improved morphology and enhanced drug loading in comparison with the aqueous medium method. The drug loading in the water-in-oil emulsion was over 30% higher than in the aqueous medium, an indication that the new method proposed the common drug leaching during the microspheres’ preparation is avoided, being an interesting alternative to encapsulate drugs of hydrophilic nature.